PROMOTION OF ADULT EDUCATION IN THE INNOVATIVE BUSINESS - Silakalne - Arāja, Daina; Arājs, Raimonds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The notions of adult education and innovative entrepreneurship have been described and analysed in the article. According to the characterization of the essence of notions, conditions of innovative entrepreneurship have been analysed. The emphasis has been put on the main problem concerning sustainable community development related to the contributions made to human resources and adult education, enabling innovative entrepreneurship oriented on the human ability to create and use their knowledge in constantly changing environmental conditions, responsible for work organisation satisfying current people’s social and economical needs, thought at the same time not endangering next generations. The following theories like the essence and process of adult education, innovations as a source of a rising viability and competitiveness and development trends of innovative activities in Latvia and the rest of the world are revealed in the article.